3D printing of shape changing composites for constructing flexible paper-based photothermal bilayer actuators. Issue 8 (12th February 2018) - Hua, Dechuan; Zhang, Xiaoqin; Ji, Zhongying; Yan, Changyou; Yu, Bo; Li, Yuandong; Wang, Xiaolong; Zhou, Feng
Abstract : Paper-based bilayer actuators with excellent light-driven shape changing performance are achieved with 3D printing of a photothermal-responsive MWCNT–PLA composite on paper. Abstract : Developing flexible shape changing actuators by means of 3D printing has become an exciting research area and has been widely used in our daily life and they are expected to play more important roles in soft robotics, biomedical devices and other high-tech areas. However, the development of such 3D printed shape changing actuators is limited due to the lack of 3D printing functional materials and insufficient response sensitivity of the actuators. This study demonstrates the 3D printing of photo-responsive shape changing composites based on polylactic acid (PLA) and multi-walled carbon nanotubes (MWCNTs) on paper substrates with fused deposition modeling (FDM) printing technology for the construction of flexible photothermal-responsive shape changing actuators. Introducing MWCNTs to a PLA matrix results in the enhancement of processabilities of the MWCNT–PLA composite during the FDM printing process compared to pure PLA. In the MWCNT–PLA composite filaments prepared in this work, MWCNTs are dispersed homogeneously in the PLA matrix. Furthermore, the MWCNT–PLA composite exhibits excellent photothermal effects and sensitivity under near-infrared irradiation (NIR), with the temperature of the composite increasing up to the T g of PLA after 1 s irradiation and also being close to the T m of PLA after irradiation for 15 s. Paper-based bilayer semicircular actuators that possess phototriggered shape changing properties are fabricated via 3D printing of the MWCNT–PLA composite on paper, which deform under near infrared irradiation and recover their original shape once the light source is switched off. This facile 3D printing strategy for flexible paper-based actuators would provide tremendous opportunities for the design and fabrication of biomimetic photothermal actuators and soft robotics.